PENGARUH PENGETAHUAN PAJAK, KEADILAN PAJAK, DAN SANKSI PAJAK PP NOMOR 46 TAHUN 2013 TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KPP BINJAI - Rumapea, Rissa; Lumban Gaol, Romasi (Jurnal Ilmiah Akuntansi (JIMAT), 2024)
This research aims to analyze the influence of tax knowledge, tax justice, tax sanctions on UMKM taxpayer compliance at KPP Pratama Binjai. The population of this research is UMKM taxpayers in Binjai who are registered at the Binjai KPP. The sample for this research is data on UMKM at KPP Binjai and tax revenues for 2017-2020 at KPP Binjai. The analytical method used is multiple linear regression analysis using the SPSS version 25 application. The results of the research show that the Tax Knowledge variable has a significant positive effect on taxpayer compliance, so that the higher the level of tax knowledge, the more obedient they will be in paying taxes. The Tax Fairness variable has a significant positive effect on Taxpayer Compliance. This proves that the more fair perceptions about taxation are formed, the higher the level of Taxpayer Compliance. The Tax Sanctions variable has a significant positive effect on Taxpayer Compliance, this proves that if the Government gives sanctions to people who do not comply with paying taxes then people will be encouraged to pay taxes.